Expert Panel on Project 5 - Ecological Effects of Human Activities on the Value and Resources of Lakes, Marshes, Rivers, Deltas, Estuaries and Coast (1972 Paris); Programme on Man and the Biosphere (Paris : Unesco, 1972)
01